Rotate-to-bend setup for fatigue bending tests on inkjet-printed silver lines. (21st August 2018) - Huber, Bernhard; Schober, Jakob; Kaiser, Michael; Ruediger, Andreas; Schindler, Christina
Abstract: For the growing field of flexible electronics the performance of fabricated flexible devices during bending deformation has to be investigated in order to guarantee their resilience against small bending radii and bending fatigue. We report on a rotate-to-bend apparatus, which allows for arbitrary sequences of compressive as well as tensile bending and a wide range of selectable bending radii without applying additional strain. The electrical characterization can be conducted simultaneously with high speed measurement. We test the rotate-to-bend device on inkjet-printed conducting paths of Ag nanoparticles and Ag nanowires on various foil substrates. Fatigue bending cycles show that tensile deformation leads to a higher increase in resistance of the printed lines compared to compressive strain. This is caused by the higher tendency of microcracks to form during tensile bending. We also show the high negative impact of the substrate thickness on bending fatigue during full bending cycles. Here, Ag nanowires show superior fatigue behaviour compared to the nanoparticle lines due to their flexible, mesh-like network. The rotate-to-bend apparatus could become an efficient and inexpensive device for the testing of flexible devices.